1975
DOI: 10.5962/bhl.title.70030
|View full text |Cite
|
Sign up to set email alerts
|

The forest-land owners of New Jersey /

Abstract: research forester, received his bachelor's degree in forestry from the University of New Hampshire in 1961 and his master's degree in forest economics from the same university in 1963. He joined the Northeastern Forest Experiment Station in August 1962. He is presently a resource analyst in the Experiment Station's Forest Survey unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Numerous landowner attitudinal surveys (e.g. Finley, 2002;Belin, 2002;White, 2001;Rickenbach et al, 1998;Kingsley, 1976;Birch, 1996) have shown that they tend to be interested in more than the former, and the latter alone caries a stigma for some; . Establishes a clear reason to cooperate, and some institutional support to get an organization through the first years of growing pains; and .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Numerous landowner attitudinal surveys (e.g. Finley, 2002;Belin, 2002;White, 2001;Rickenbach et al, 1998;Kingsley, 1976;Birch, 1996) have shown that they tend to be interested in more than the former, and the latter alone caries a stigma for some; . Establishes a clear reason to cooperate, and some institutional support to get an organization through the first years of growing pains; and .…”
Section: Discussionmentioning
confidence: 97%
“…Birch, 1996;Alexander, 1986;Rickenbach et al, 1998;Tyson et al, 1998;Bourke and Luloff, 1994;Jones et al, 1995;Finley, 2002;Kingsley, 1976;Egan, 1998). All of these benefits can be enhanced by planning and managing forests at spatial scales that are larger than an individual property.…”
Section: Why Cooperate?mentioning
confidence: 92%
See 1 more Smart Citation
“…Forest owners tended to be old and land tenure and inheritance became issues [47,48]. Level of education has always been shown to be positively linked to better forest management, probably due to its correlation with forest owner financial position [41,[50][51][52][53][54][72][73][74]. Other variables that were usually in forest owner surveys were length of land tenure [40], distance of residence from the forest [39,75], proximity to an example of well-managed forest land [39,77], primary objective of management [40,71], understanding of forestry concepts [38,76], and size of forest holding [41].…”
Section: Classical Nipf Ownership Characteristics and Related Forest mentioning
confidence: 99%
“…Not surprisingly, asset or financial position (or a proxy for asset position, like size of forest holding) often was found to be an important determinant of landowner behavior [13,42]. Plus, a number of studies showed that many NIPF owners did not primarily focus on timber production, but had major ownership objectives related to non-timber outputs like wildlife and recreation [51,92,104,105,112,134,[145][146][147][148][149][150][151][152][153][154][155][156][157][158][159]. Even forest landowners' stated intentions were found to differ from later forest management practices on the ground [152][153][154][155].…”
Section: Classical Nipf Ownership Characteristics and Related Forest mentioning
confidence: 99%